Spatial dynamics of ambrosia beetle infestations in avocado orchards: a geostatistical approach from Indonesia - Yahya, Minhajul Qowim; Setiawan, Yogo; Hadi, Mochammad Syamsul; Tarno, Hagus (Journal of Plant Protection Research, 2026)
Ambrosia beetles (Coleoptera: Scolytinae and Platypodinae) represent a significant threat to tropical agroecosystems, yet their spatial ecology in Indonesian avocado orchards remains poorly understood. This study presents the first spatially explicit assessment of ambrosia beetle infestation patterns in East Java, integrating field surveys with geostatistical analyses. Using RStudio and spatial tools including kernel density estimation (KDE), density-based spatial clustering of applications with noise (DBSCAN) clustering, and Getis-Ord Gi* statistics, this research was aimed to distinguish spatial clusters, evaluate environmental correlates such as sunlight exposure, infestation holes vertical level position based on tree trunk, and recognize tree trunk diameter-related preferences in colonization of the ambrosia beetles. Results revealed strong spatial aggregation of beetle attacks, with significantly higher infestation intensity observed in trees exposed to prolonged sunlight, infestation holes located in upper trunk positions, and possessing larger tree trunk diameters. Global Moran’s I and LISA statistics confirmed significant clustering, validating the influence of orchard microheterogeneity on beetle colonization. These findings underscore the importance of integrating spatial analysis into pest management strategies and offer a replicable framework for monitoring cryptic pests in other tropical cropping systems.